Desmophyllum dianthus relative and absolute fatty acid and fatty alcohol composition in Comau Fjord, Chile - Marlene Wall; Kristina K Beck; Nur Garcia-Herrera; Gertraud M Schmidt-Grieb; Jürgen Laudien; Juan Höfer; Günter Försterra; Christoph Held; Gernot Nehrke; Juan Pablo Espinoza; Matthias Woll; Martin Graeve; et al. (PANGAEA, 2023)
In September 2016 specimens of the cold-water coral Desmophyllum dianthus were sampled along natural oceanographic horizontal and vertical gradients (vertically: 20 m and 280 m depth and horizontally: fjord head, center, and mouth) in Comau Fjord to study its fatty acids composition. The aim was to understand better a) how the fatty acid composition changes in response to the experienced in situ environmental conditions, b) if they can provide insights into the potential food sources, and c) how the coral phenotype affects their composition. The background environment conditions and the coral extquotesingles physiological performance were derived from previous assessments (Beck et al. 2022, doi:10.1594/PANGAEA.945072), and additional CTD casts were performed in September 2016 (doi:10.1594/PANGAEA.962593).